Exploring scenarios to facilitate the access to 3D printing technology through sustainable product-service systems in the Egyptian maker market - Mohamed, Doaa (AUC Knowledge Fountain, 2019)
The research aims to investigate two models: Sustainable Product Service System (S.PSS) applied to Distributed Manufacturing (DM). S.PSS aims to combine environmental with social and economic sustainability to achieve social equity in low and middle-income contexts through a system design of products and services satisfying the market demand. DM allows the organization of connected small scale and flexible production units to share various forms of resources (tangible or intangible), while using emerging technologies. The combined models aim to address the environmental, social and economic issues in low and middle-income contexts by offering new opportunities for young makers who wish to be entrepreneurs to develop sustainable local startups. The research started by covering past work about approaches, opportunities and barriers of the two models through literature review. Then, a collection of international cases of small-scale production were studied further and other case studies in the Egyptian context were formulated. The Egyptian case studies were based on qualitative methods (mainly in-depth interviews, observational research and reflective field notes) and investigated the operational tactics of PSS to fill research gap. Participatory workshops were held to discuss the possible scenarios for applying the coupled models in business, especially in the field of Additive Manufacturing. Later, experts were interviewed to discuss whether the scenarios are applicable in a low and middle-income market like Egypt. The outcome is a sustainable design-oriented scenario (from proposed near-future scenarios) that reflects the advantages of S.PSS applied to DM for the Sustainable Development in low and middle-income contexts; in addition to a set of guidelines for applying these scenarios to support makers' market. The scenarios and guidelines are to fill the research gaps found in previous studies discussing the mentioned models and to pave the way for future studies with same focus.